2017
DOI: 10.1002/mp.12623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PET/CT system, reconstruction protocol, data analysis method, and repositioning on PET/CT precision: An experimental evaluation using an oncology and brain phantom

Abstract: PurposeIn longitudinal oncological and brain PET/CT studies, it is important to understand the repeatability of quantitative PET metrics in order to assess change in tracer uptake. The present studies were performed in order to assess precision as function of PET/CT system, reconstruction protocol, analysis method, scan duration (or image noise), and repositioning in the field of view.MethodsMultiple (repeated) scans have been performed using a NEMA image quality (IQ) phantom and a 3D Hoffman brain phantom fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…This similarity is remarkable as the parameters rely on uptake information derived from substantially different volumes (75 mm 3 vs. 1 cm 3 in our study). In general, due to its small size, SUV max is known to be adversely affected by noise and to be sensitive to respiratory motion artifacts that naturally occur during PET acquisition [26,27]. SUV peak on the other hand is less affected by these inherent disadvantages of SUV max and thus preferred by some authors [5]; in contrast, however, SUV peak is more prone to partial volume effects [5].…”
Section: Discussionmentioning
confidence: 99%
“…This similarity is remarkable as the parameters rely on uptake information derived from substantially different volumes (75 mm 3 vs. 1 cm 3 in our study). In general, due to its small size, SUV max is known to be adversely affected by noise and to be sensitive to respiratory motion artifacts that naturally occur during PET acquisition [26,27]. SUV peak on the other hand is less affected by these inherent disadvantages of SUV max and thus preferred by some authors [5]; in contrast, however, SUV peak is more prone to partial volume effects [5].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the radioactivity of a small region are strongly affected by the partial-volume effect (19). Mansor et al reported that the precision of SUV max was affected by phantom repositioning in a study that used hot spheres of # 15 mm in diameter (20). Furthermore, Adams et al reported that the measured PET count varied and that there was a relationship between the alignment of the hot spot and the pixels (21).…”
Section: Discussionmentioning
confidence: 99%
“…From the full range GLCMs, 11 Haralick or so called second-order statistical features were calculated and plotted against exposure (Eqs 12-22). The resulting scatterplots were smoothed by the LOESS method to obtain differentiable curves for every feature (Fig 5).…”
Section: Exposure Dependency Of Haralick Featuresmentioning
confidence: 99%
“…However, images-and hence the measured tracer uptake values-typically differ between the various clinical PET/CT systems, even when imaging the very same object [10]. Distinct instrumentation and differences in image reconstruction algorithms impart characteristic imaging properties to PET/CT systems [11]. Resultant differences in imaging properties limit the comparability of datasets acquired on different PET/CT systems or with different acquisition protocols, and hamper the use of quantitative tracer uptake values in clinical routine or in multicenter clinical trials [12].…”
Section: Introductionmentioning
confidence: 99%